Assembly and test of prototype scintillator tiles for the plastic scintillator detector of the High Energy Cosmic Radiation Detection (HERD) facility. Issue 1 (1st November 2022) - Altomare, C.; Alemanno, F.; Barbato, F.C.T.; Bernardini, P.; Cattaneo, P.W.; De Mitri, I.; de Palma, F.; Dipinto, P.; Di Venere, L.; Di Santo, M.; Fusco, P.; Gargano, F.; et al.
Abstract : Satellite experiments for gamma-ray and cosmic-ray detection employ plastic scintillators to discriminate charged from neutral particles in order to correctly identify gamma-rays and charged nuclei. The High Energy Cosmic Radiation Detection (HERD) facility will be among these experiments, to be installed onboard the future Chinese Space Station (CSS), to detect cosmic-rays and gamma-rays up to TeV energies. The plastic scintillator detector (PSD) will consist of scintillator tiles or bars coupled to Silicon Photomultipliers (SiPMs). To discriminate gamma-rays from charged particles and measure the ion charge up to iron nuclei a wide dynamic range is required, from few tens up to thousands of photoelectrons. We have equipped a plastic scintillator tile prototype with SiPMs produced by Hamamatsu and AdvanSiD and coupled their analog signals to the DT5550W board based on the CITIROC ASIC, produced by CAEN SpA. The CITIROC ASIC allows both the formation of a fast trigger with a configurable threshold and the digitization of analog waveforms after a preamplification and shaping stage along two paths with different gain settings. The performance of our prototype will be shown.